196k views
2 votes
I don't know what to do. This is about odd and even functions.

I don't know what to do. This is about odd and even functions.-example-1

2 Answers

6 votes
The answer will be C
User Vinayrks
by
4.5k points
5 votes

Answer:

C.

Explanation:

We are given
f,g are odd which means:


f(-x)=-f(x)


g(-x)=-g(x)

We can tell if a function,
h, is even if
h(-x)=h(x).

We can tell if a function,
h, is odd if
h(-x)=-h(x).

So let's test your I,II,III.

We will be replacing x with -x to find out.

I.


p(x)=f(g(x))


p(-x)=f(g(-x))


p(-x)=f(-g(x))


p(-x)=-f(g(x))


p(-x)=-p(x)

So
p is odd.

II


r(x)=f(x)+g(x)


r(-x)=f(-x)+g(-x)


r(-x)=-f(x)+-g(x)


r(-x)=-(f(x)+g(x))


r(-x)=-(r(x))


r(-x)=-r(x)

So
r is odd.

III


s(x)=f(x)\cdot g(x)


s(-x)=f(-x) \cdot g(-x)


s(-x)=-f(x) \cdot -g(x)


s(-x)=f(x) \cdot g(x)


s(-x)=s(x)

So
s is even.

So I and II are odd and III is even.

C. is the answer.

User IJeep
by
4.4k points